Bilateral Integrative Medicine, Obviously - Steven H. Stumpf (Evidence-Based Complementary and Alternative Medicine, 2006)
Unstated and unacknowledged bias has a profound impact on the nature and implementation of integrative education models. Integrative education is the process of training conventional biomedical and traditional Chinese medicine practitioners in each tradition such that patient care may be effectively coordinated. A bilateral education model ensures that students in each tradition are cross-taught by experts from the ‘other’ tradition, imparting knowledge and values in unison. Acculturation is foundational to bilateral integrative medical education and practice. Principles are discussed for an open-minded bilateral educational model that can result in a new generation of integrative medicine teachers.